Culture, globalisation and national development (2014)
In several publications, CLR James, the Trinidadian Pan-Africanist and writer, affirms that persons of African descent in the new world squarely belong in the historiography of the Western world and now have a Western identity. To this end, their empirical, positivist world is Western, since then- day to day living is now in their various nationalities which are geographically situated in the Northern hemisphere. As a researcher and culturalist, one is inspired to seek confirmation or denial of this assertion, since the speaker was himself, both a Caribbean citizen and a Pan-Africanist. However, CLR James’s assertion, apart from raising both identity and methodological questions, implies that we live in a plural world where we have multiple clustered identities. The notion of being African also encompasses the notion of being larger than Africa. The whole enterprise of Diaspora Studies must, therefore, invent such principles and methods that go beyond the nonnative or given parameters that we are hitherto used to. In the present enterprise, the study of history automatically invokes the excavation of African and Diaspora philosophy and psychoanalysis. It is in this form of advocacy that we can enrich that which sees itself as either African or diasporic. On a global scale, we should be able to apply identity categorization to who we are in our particular as well as various nations. In Nigeria, for instance, how do we claim to be a member of our ethnic group as well as a citizen of Nigeria? It is not a question of which comes first, but which supersedes the other on each given occasion